Contingent Valuation of Watershed Protection in Nigeria: A Case Study - Femi Olokesusi (Indonesian Journal of Geography, 1994)
The search for appropriate methods for valuing natural resources and monctising externalities is a pressing problem facing many governments, particularly those of the developing countries. While the Nigerian government allocates 2% of its annual gross income for ecological damage restitution (The Ecological Fund), experiences arising from incessant disputes in the oil producing areas, fishing sites, increasing incidence of soil erosion and flooding and other environmental problems, all point to the need to supplement the Ecological Fund with money from other sources.Most environmental degradation resulting from mithropogenic prococcrs in water resource projects can be ascribed to the "common property" perception of water and associated natural resources. Moreover, in deciding which environmental regulations, and water resource projects and programmes are desirable or otherwise, it is imperative to weigh the negative socio-economic impacts, againts the very real beneficial effects. Such a process will entail better monetary quantification of the cost-benefit analysis of the projects and programmes, particularly during environmental impact assessment process.This paper focusses on the use of the willingness-to-pay (WTP) approach for determining the amount of money that people in selected large-scale irrigation and dam project areas in the Sudano-Saludian zone of Nigeria are willing to forego for the sake of environmental protection in the watershed. After a general description of the problems and approaches to valuing and monetising environmental resources and their protection, the details of the study findings and policy implications are discussed.